Triatomines outside the Americas: a comprehensive dataset for the global surveillance of Chagas disease vectors - Soledad Ceccarelli; Maria Eugenia Vicente; Qin Liu; Xiao-Nong Zhou; Di Wu; Agustin Balsalobre; Emiliano A. Bruno; S. Emilia Barboza; Romina Valente; Gerardo A. Marti (GigaByte)
Chagas disease is caused by Trypanosoma cruzi, which is transmitted to mammals, including humans, mainly by insects of the subfamily Triatominae (Hemiptera: Reduviidae). Also known as “kissing bugs”, the subfamily includes 159 species in 18 genera and five tribes. Although most species are in the Americas, here we present the first compilation of non-American triatomine occurrences. The data (396 records) corresponds to 16 species of the genera Linschosteus and Triatoma from Africa, Asia, and Oceania collected between 1926 and 2022, and include verified records with geographic coordinates, collection dates, and ecological information. The key novelties of our dataset regard (i) temporal and geographical updates of non-American species, (ii) records of T. rubrofasciata hundreds of kilometers inland, and (iii) geographical records of the last two described Triatoma species (T. atrata and T. picta). Our resource supports global surveillance, ecological modeling, and risk assessment by providing evidence of potential vectors for Chagas disease control outside the Americas.